Novel Pyrazine-Bridged D-A-D Type Charge Neutral Probe for Membrane Permeable Long-Term Live Cell Imaging - Liu, Pei; Chen, Suna; Zhao, Wenxuan; Wang, Qiutang; Wu, Shuqi; Xu, Liang; Bai, Dan (Frontiers in Chemistry, 2021)
A novel donor-acceptor-donor (D-A-D) type compound containing pyrazine as acceptor and triphenylamine as donor have been designed and synthesized. The photophysical properties and biocompatibility of this probe namely (OMeTPA)2-Pyr for live cell imaging were systematically investigated, with observed large Stokes shifts, photostability and low cytotoxicity. Furthermore, we demonstrated that (OMeTPA)2-Pyr could permeate living cells and long-term label cells, with proposed mechanism of shafting through typeII membrane integral transport proteins through electrostatic and hydrophobic interactions. These salient and novel findings can facilitate the strategic design of new pyrazine fused charge neutral molecular platforms as fluorescent probes for long-term monitoring of live cells.